Penyuluhan untuk Peningkatan Kualitas Hidup Penyintas Covid-19 di Wilayah Kerja Puskesmas Rejosari Pekanbaru - Armoni Suci Dewi; Inten Laras Satiti; Iwed Mulyani (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
After recovering from COVID-19, patients can experience long-term COVID-19, which is a condition where there is a residual effect from COVID-19 infection. This long-term COVID-19 condition has an impact on a person's quality of life. In the preliminary study, a qualitative approach was used with descriptive analysis in a case study. Data were collected through structured interviews. The informants involved were 20 COVID-19 survivors in the Rejosari Health Center area and the team in charge of Epidemiological Investigation and Health Promotion, Rejosari Health Center. The preliminary study results showed that 20 COVID-19 survivors experienced a decrease in quality of life from 9.0 when not infected to 8.3 after being declared cured of the infection. In addition, the evaluation found that the Rejosari Health Center had never conducted counseling to improve the quality of life for COVID-19 survivors in its working area. The purpose of this activity is to provide counseling using the Plan, Do, Check, and Action (PDCA) cycle method for COVID-19 survivors in the working area of ​​the Rejosari Health Center. The plan of action stage in the form of counseling and dissemination of information media in the form of electronic pocketbooks and educational videos about improving the quality of life of COVID-19 survivors has been carried out. Then, the evaluation results of increasing public knowledge from 16 people (45.7%) less knowledgeable to 28 people (80%).